2020
DOI: 10.21873/anticanres.14282
|View full text |Cite
|
Sign up to set email alerts
|

Second-line Treatment in Advanced Biliary Tract Cancer: Today and Tomorrow

Abstract: Biliary tract cancer (BTC) patients usually have poor prognosis. Whereas combination chemotherapy has been shown to improve survival in the frontline setting, second-line treatment is subject to a lot of debate in the scientific community. Recent data of the ABC-06 trial has provided slight evidence for the use of second-line chemotherapy after progression on cisplatin plus gemcitabine combination. In this study, mFOLFOX plus active symptom control (ASC) improved overall survival (OS) after progression on cisp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
46
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 108 publications
0
46
0
1
Order By: Relevance
“…A statistically significant (P = 0.031) and clinically meaningful improvement in OS was observed in patients treated with ASC plus mFOLFOX versus ASC alone. Another chemotherapy regimen, FOLFIRINOX, demonstrated efficacy in a phase 2 trial of patients with BTC who had experienced disease progression following treatment with cisplatin and gemcitabine: median PFS and OS were 6.2 and 10.7 months, respectively [23,24]. Also, Abou-Alfa et al [25] evaluated ivosidenib versus placebo in patients with advanced cholangiocarcinoma (primarily intrahepatic) and an isocitrate dehydrogenase 1 (IDH1) gene mutation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A statistically significant (P = 0.031) and clinically meaningful improvement in OS was observed in patients treated with ASC plus mFOLFOX versus ASC alone. Another chemotherapy regimen, FOLFIRINOX, demonstrated efficacy in a phase 2 trial of patients with BTC who had experienced disease progression following treatment with cisplatin and gemcitabine: median PFS and OS were 6.2 and 10.7 months, respectively [23,24]. Also, Abou-Alfa et al [25] evaluated ivosidenib versus placebo in patients with advanced cholangiocarcinoma (primarily intrahepatic) and an isocitrate dehydrogenase 1 (IDH1) gene mutation.…”
Section: Discussionmentioning
confidence: 99%
“…However, a pilot study of sorafenib versus best supportive care in patients with advanced intrahepatic cholangiocarcinoma demonstrated sorafenib has antitumor activity with a median PFS of 3.2 months (95% CI: 2.4-4.1) and median OS of 5.7 months (95% CI: 3.7-8.5) [26]. Additionally, several phase 2 trials evaluating tyrosine kinase inhibitors, such as apatinib (NCT03521219), infigratinib (NCT02150967), derazantinib (NCT03230318), erdafitinib (NCT02699606), and pemigatinib (NCT04256980), as second-line treatment options in patients with BTC are currently ongoing [23].…”
Section: Discussionmentioning
confidence: 99%
“…Systemic chemotherapy is the backbone of palliative treatment for BTC patients, with the combination of cisplatin plus gemcitabine representing the current standard of care in the front-line setting, following the results of the ABC-02 trial [ 9 ]. Although this phase III trial showed a survival advantage for cisplatin–gemcitabine over gemcitabine monotherapy, nearly all BTC patients develop progressive disease during first-line treatment, with a median overall survival (OS) of less than a year [ 10 ]. Thus, improving outcomes in patients affected by advanced/metastatic BTC represents an urgent need.…”
Section: Introductionmentioning
confidence: 99%
“…As previously stated, previous experiences in ovarian and breast cancer have paved the way toward a number of trials testing PARPi in several tumors, with PARPi that are currently under active evaluation also in BRCA-mutated biliary malignancies [ 8 , 9 , 10 ]. However, a larger spectrum of genes that compromise DDR pathway has been reported to occur in up to 28.9% of patients with newly diagnosed BTC, and to date, the optimal therapeutic strategy in BTC tumors harboring Homologous Recombination Deficiency (HRD) alterations is yet to be defined [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…6 And to date, only a limited number of studies have been performed to assess efficacy of ICIs in BTC, with available clinical data mainly limited to sub-analyses of basket trials and small single-arm trials. 7 Thus, immunotherapy is still looking for its niche in BTC.…”
mentioning
confidence: 99%